Relationship Between Hand Kinematics, Hand Hydrodynamic Pressure Distribution and Hand Propulsive Force in Sprint Front Crawl Swimming - Koga, Daiki; Tsunokawa, Takaaki; Sengoku, Yasuo; Homoto, Kenta; Nakazono, Yusaku; Takagi, Hideki (Frontiers in Sports and Active Living, 2022)
Purpose: This study investigated the relationship between hand kinematics, hand pressure distribution and hand propulsive force when swimming the front crawl with maximum effort. Methods: Twenty-four male swimmers participated in the study, and the competition levels ranged from regional to national finals. The trials consisted of three 20 m front crawl swims with apnea and maximal effort, one of which was selected for analysis. Six small pressure sensors were attached to each hand to measure the pressure distribution in the hands, 15 motion capture cameras were placed in the water to obtain the actual coordinates of the hands. Results: Mean swimming velocity was positively correlated with hand velocity (r = 0.881), propulsive force (r = 0.751) and resultant force (r = 0.687). Pressure on the dorsum of the hand showed moderate negative correlations with hand velocity (r = -0.720), propulsive force (r = -0.656) and mean swimming velocity (r = -0.676). On the other hand, palmar pressure did not correlate with hand speed or mean swimming velocity. Still, it showed moderate positive correlations with propulsive force (r = 0.512), resultant force (r = 0.736) and angle of attack (r = 0.471). Comparing the absolute values of the mean pressure of the palm and the dorsum of the hand, the mean pressure of the dorsum was significantly higher and had a larger effect size (d = 3.71). Conclusion: It is suggested that higher hand speed resulted in a more significant decrease in dorsal pressure (absolute value greater than palmar pressure), increasing the hand propulsive force and improving mean swimming velocity.